Peningkatan Daya Saing Siswa Menengah Kejuruan Swasta melalui Pelatihan Regulasi Diri - Sakti, Hastaning; Ariati, Jati (Jurnal Psikologi, 2014)
The aim of this research was to design self-regulation training as an alternative effort to enhance students’ competitiveness. A total number of 147 students from two private vocational schools were involved as subjects. Pretest posttest control group design was used. In each school there were an experimental group, which got self-regulation training, and a control group, which got self-concept training. Manipulation was delivered six times each of which was supervised by two observers. T-test showed there were differences between experimental groups. SMK PL: before (M=89.93, SD=7.681) and after manipulation (M=92.16, SD=7.278) t(43) =-2.185, p